Growth of Healthy Term Infants Fed an Extensively Hydrolyzed Casein-Based or Free Amino Acid–Based Infant Formula: A Randomized, Double-Blind, Controlled Trial. (October 2013) - Borschel, Marlene W.; Ziegler, Ekhard E.; Wedig, Rita Thomas; Oliver, Jeffery S.
A masked, randomized, parallel growth study was conducted in infants fed an amino acid–based formula (AF) or an extensively hydrolyzed casein-based formula (HF). Infants were enrolled between 0 and 9 days and studied to 112 days of age. Growth, formula intake, stool patterns, and serum albumin concentrations were assessed. There were no significant differences between groups in weight, length, or head circumference, gains in weight or length, or study formula intake. The number of stools parents rated as being formed, and the mean daily number of stools were greater in the HF than in the AF group at 14 and 28 days of age. Mean serum albumin concentrations were not significantly different between groups and were within the normal range. This study demonstrates that AF supports normal growth of infants comparable to that of infants fed HF during the critical first 4 months of life.